Associations between Traditional and Digital Leadership in Academic Environment: During the COVID-19 Pandemic - Hera Antonopoulou; Constantinos Halkiopoulos; Olympia Barlou; Grigorios N. Beligiannis (Emerging Science Journal, 2021)
Objectives: Notably, as a result of the unique circumstances that the global population is facing (Covid-19), there has been an increase in interest in educational leadership science, particularly in academic environment, with the aim of enhancing an ecosystem that is inclusive, open to change, monitoring, and often unforeseen challenges. Of the various types of educational leadership, transformational leadership is recognized as the most suitable for use in academic environment. It focuses on the division of leadership responsibilities among academics with varying skills in order to handle collectively the spectrum of leadership responsibilities needed in a variety of contexts. Methods/Analysis: This perspective is embodied in this study paper, which examined the degree to which members of the Senate of three Universities of Greece, engaged in three distinct types of leadership (transformational leadership, transactional leadership, and leadership to be avoided) via digital leadership. The findings were interpreted using descriptive, diagnostic, predictive and prescriptive data analysis algorithms. Findings: The findings indicate that participants demonstrate a high level of Transformational and Transactional Leadership. They demonstrated a high level of Digital Leadership while avoiding Passive - To Avoid Leadership. The study demonstrates that Digital Leadership has a relatively favorable association with the leadership outcome, which is translated as a high level of performance and satisfaction coexisting with a high level of digital leadership execution. Novelty /Improvement: The research project indicates that a good leader who practices transformational leadership and is prepared with the necessary digital skills would be more effective in carrying out administrative responsibilities in an academic environment. Doi: 10.28991/esj-2021-01286 Full Text: PDF